Desarrollo de un Objeto Virtual de Aprendizaje OVA (DVD interactivo) para el entrenamiento en las técnicas de exploración clínica en rumiantes domésticos (2023)
In teaching processes used in Veterinary Medicine and Zootecnics faculties, information and communication technologies (ICT) are implemented, even though the development of these in society is not concordant. As a result, there are still educators and students who are resistant to the change, have a lack of interest in it, are unfamiliar and/or lack the capacity of the technical or didactic use of these ICTs. The ICTs are also an alternative and independent learning approach for the students which facilitate interacting with reality from the classroom. In addition to being a bioethical alternative to the use of animals in practices, they allow a high quality education which replaces or reduces the number of live animals used in academic practices. Looking for a modern alternative, attractive to the student, in the framework of bioethics, an interactive DVD was created for training in clinical exploration techniques in domestic ruminants. Videos produced by students were collected as evidence in the semiotics course of the Faculty of Veterinary Medicine and Zootecnics of the Universidad Cooperativa de Colombia (UCC) in Bucaramanga, Colombia. Of the 157 videos collected from the years 2008, 2009, 2010 and 2011, 72 videos of cattle, goats and sheep were selected according the quality of the audio, image and content. An interface was created through Adobe Flash Player CS. A test was conducted with students from semesters VI and IX of the Veterinary Medicine and Zootecnics Faculty, who evaluated the interactive DVD using a qualitative perception questionnaire which collected information on design, content and preference, obtaining good results in acceptance, perception and relevance and design of the interactive DVD.